Behavior-Based Approach for the Detection of Land Mines Utilizing off the Shelf Low Cost Autonomous Robot - Abdel Ilah Nour Alshbatat (IAES International Journal of Robotics and Automation (IJRA), 2013)
Several countries all of the world are affected by landmines. The presence of mines represents a major threat to lives and causes economic problems. Currently, detecting and clearing mines demand specific expertise with special equipment. In this context, this paper offers the design and development of an intelligent controller which can control and enable the robot to detect mines by means of sensors and of processing the fused information to guide soldiers when passing landmines.  This is accomplished by broken down the overall system into two subsystems: sensor technologies and robotic device. Sensors devices include infrared distance sensor, metal detector, ultrasonic range finder, accelerometer sensor, while the structure of the robot in our case consists mainly  of a commercial  off-the-shelf  parts which  are  available  at  low  costs. The proposed controller is mainly based on creating fuzzy rules that reflect the behaviors of soldier beings in controlling a robot in a well known landmine. Simulation and experimental results are presented her to prove the efficiency of the proposed approach. The results show that the system is able to detect landmines and guide soldiers while crossing mines area.